Optimising the seed production cycle of Delphinium elatum L. : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Plant Biology at Massey University, Palmerston North - Bedford, Katharine (Massey University, 2005)
Delphinium elatum L. (Ranunculaceae) hybrids are developed by Dowdeswell's Delphiniums located at 692 Brunswick Road. Wanganui (www.delphinium.co.nz), who grow delphiniums for seed export. Development of new cultivars is important for commercial purposes, and requires development of high quality breeds. The main objectives of this study were to determine reasons for variable seed set and low germination in commercial D. elatum hybrids and determine optimal parameters for seed germination and storage. Seed set was investigated by examining pollen viability, carpel structure, and pollen tube growth in vitro and in vivo. Seed structure was determined by paraffin embedding and sectioning of seeds. Results investigating variable seed set were inconclusive. Seed set is limited by pollen viability and age. Pollen viability is low (below 50%) in most cultivars, and pollen tubes growth rate is variable between cultivars and individual pollen grains. Ovule development showed no abnormalities. Germination-promoting treatments were used to improve germination in D. elatum. Stratification (5°C) and application of gibberellic acid both improved germination in D. elatum cultivars. Chilling at 5°C reduced germination time in all cultivars, and increased total germination in cv. LB01130x. Storage trials were carried out for 12 months, with seeds stored at room temperature or 5°C in open and closed, water impermeable, aluminium bags. Storage trials determined that at low temperature storage (5°C) seed germinability is retained for up to 12 month. Storage at room temperature leads to seed deterioration and viability loss. Application of GA3 improved germination in seed stored at 5°C.
Keywords: New Zealand Seed technology; Delphinium -- Seeds; Quality; Viability; Storage; Reproduction